ANALISIS YURIDIS DAMPAK REGULASI IMPOR PAKAIAN BEKAS TERHADAP PELAKU USAHA THRIFTING DI KOTA PONTIANAK - NIM. A1011211270, RADEN FALYA PARADIANI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This study analyzes the legal framework governing the import regulation of secondhand clothing in Indonesia and its socio-economic implications for the community in Pontianak City. The research focuses on regulations such as Minister of Trade Regulation Number 51 of 2015 and Number 40 of 2022, which explicitly prohibit the import of secondhand clothing to protect domestic industries, public health, and the environment. The study employs an empirical legal method with a qualitative approach. Primary data was collected through questionnaires completed by 10 secondhand clothing sellers and 10 buyers in Pontianak City, while secondary data includes legal documents such as Minister of Trade Regulation Number 51/M-DAG/PER/7/2015 on the Prohibition of Importing Secondhand Clothing, the Consumer Protection Law, the 1945 Constitution, and academic journals. The data analysis technique is descriptive, aiming to identify patterns and themes from the respondents' answers and their relevance to the existing regulatory framework. The research population includes 10 samples of secondhand clothing business actors and 10 samples of secondhand clothing consumers. The findings reveal the actual conditions: despite the legal prohibition, the trade of secondhand clothing remains widespread in Pontianak, serving as the primary source of income for 90% of sellers (mainly from low-income groups). Consumers (80%) prefer affordable prices and model variety despite health risks and environmental impacts. The main challenges include weak law enforcement and lack of inter-agency coordination regarding the ban on secondhand clothing imports. The conflict between legal compliance and livelihood needs creates a socio-economic dilemma, where repressive regulations without alternative solutions only exacerbate inequality. A balanced approach is needed: strict supervision and the empowerment of local MSMEs through sustainable fashion training. Policies must align the law with socio-economic realities to ensure justice for the people of Pontianak. (Keywords: secondhand clothing, import regulation, socio-economic impact, public health, Pontianak) Abstrak Penelitian ini menganalisis kerangka yuridis regulasi impor pakaian bekas di Indonesia dan implikasi sosial-ekonominya bagi masyarakat Kota Pontianak. Fokus penelitian mencakup regulasi seperti Peraturan Menteri Perdagangan Nomor 51 tahun 2015 dan Nomor 40 tahun 2022 yang secara tegas melarang impor pakaian bekas untuk melindungi industri dalam negeri, kesehatan masyarakat, dan lingkungan. Penelitian menggunakan metode hukum empiris dengan pendekatan kualitatif. Data primer diperoleh melalui kuesioner yang diisi oleh 10 pedagang dan 10 pembeli pakaian bekas di Kota Pontianak, sementara data sekunder mencakup analisis dokumen hukum seperti Peraturan Menteri Perdagangan Nomor 51/M-DAG/PER/7/2015 mengenai Larangan Impor Pakaian Bekas, Undang-Undang Perlindungan Konsumen, Undang-Undang Dasar 1945, dan Jurnal. Teknik analisis data dilakukan secara deskriptif untuk mengidentifikasi pola dan tema dari respons responden serta relevansinya dengan kerangka regulasi yang berlaku. Dengan populasi penelitian meliputi 10 sample pelaku usaha pakaian bekas dan 10 sample pembeli pakaian bekas. Hasil temuan mengungkap kondisi nyata yaitu, meski ada larangan hukum, perdagangan pakaian bekas tetap marak di Pontianak menjadi sumber penghasilan utama bagi 90% pedagang (terutama kelompok berpenghasilan rendah). Konsumen (80%) memilih harga murah dan variasi model meski risiko kesehatan dan dampak lingkungan. Tantangan utama: kurangnya penegakan hukum dan kurangnya koordinasi antarlemabaga mengnai lerangan impor pakaian bekas. Konflik antara kepatuhan hukum dan kebutuhan hidup menciptakan dilema sosial-ekonomi, di mana regulasi yang bersifat represif tanpa solusi alternatif justru memperburuk kesenjangan. Diperlukan pendekatan seimbang: pengawasan ketat, dan pemberdayaan UMKM lokal melalui pelatihan fashion berkelanjutan, Kebijakan harus menyelaraskan hukum dengan realitas sosial-ekonomi untuk keadilan bagi masyarakat di Pontianak. (Kata kunci: pakaian bekas, regulasi impor, dampak sosial-ekonomi, kesehatan masyarakat, Pontianak)